2014
DOI: 10.6065/apem.2014.19.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Age of menarche and near adult height after long-term gonadotropin-releasing hormone agonist treatment in girls with central precocious puberty

Abstract: PurposeGonadotropin-releasing hormone agonist (GnRHa) is known for improving final adult height in patients with central precocious puberty (CPP). This study aimed to investigate the age of menarche and near adult height in girls with CPP who had been treated with GnRHa.MethodsIn this retrospective study, we reviewed the medical records of 71 Korean girls with CPP who had started menarche or reached over 13 years of bone age after long-term GnRHa treatment. We estimated near adult height using the Bayley-Pinne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…In the 75 patients who completed GnRH agonist treatment, their midparental height was 159.53 ± 3.78 cm; their pre-and post-treatment PAH were 154.52 ± 5.78 and 163.48 ± 5.19 cm, respectively; and their PAH increase was 8.96 ± 5.04 cm. These findings are consistent with previous reports [27][28][29][30]. Unfortunately, data on the actual final height are not yet available, since the vast majority of patients have not yet reached their final height.…”
Section: Discussionsupporting
confidence: 92%
“…In the 75 patients who completed GnRH agonist treatment, their midparental height was 159.53 ± 3.78 cm; their pre-and post-treatment PAH were 154.52 ± 5.78 and 163.48 ± 5.19 cm, respectively; and their PAH increase was 8.96 ± 5.04 cm. These findings are consistent with previous reports [27][28][29][30]. Unfortunately, data on the actual final height are not yet available, since the vast majority of patients have not yet reached their final height.…”
Section: Discussionsupporting
confidence: 92%
“…For the first time a mean interval between cessation of therapy and starting of menarche could be shown for a bigger group of girls with WBS. This interval was 11 months on average and did not differ from other groups of patients (17)(18)(19) When looking at weight development, it could be shown that prepubertally girls were normal weight in both groups, whereas in adulthood in the majority of patients they were overweight/obese (Tables 1 and 2). There was no significant difference in BMI between both groupsneither in prepubertal stage nor in adulthood.…”
Section: Discussionmentioning
confidence: 70%
“…An average interval of 0.9-1.5 years was required for the onset of menarche after treatment cessation, and menarche started at approximately 12.6-13.6 years old in chronologic age. In a Korean study, Baek et al 12) reported that menarche began at approximately 14 months post-GnRHa treatment, which was 11.9 years in chronologic age and 12.8 years in bone age; these ages are similar to the average age at menarche among normal girls in Korea (12.6 years). When patients were stratified according to their age at CPP diagnosis (age under 6 groups, age 6-8 groups, and age 8-9 groups), the repuberty period and onset of menarche after treatment were similar regardless of the age at diagnosis 8 , 10 , 17) .…”
Section: Time Of Menarche After Treatment Discontinuation and Reprodumentioning
confidence: 79%
“…Kwon et al 11) reported that after tracking CPP patients who had received an average of 2.5 years of GnRHa treatment for approximately 3.4 years, the PAH increased by approximately 5 cm in 2 years and approximately 6-7 cm in 3 years after treatment 11) . Another study showed that the near adult height increased by approximately 5.1 cm, compared with the PAH in CPP patients after GnRHa treatment 12) . A long-term study involving Korean CPP patients is needed to examine the effect of treatment on final adult height gains.…”
Section: Final Heightmentioning
confidence: 98%